Can foliar application of seaweed sap improve the quality of rice grown under rice–potato–greengram crop sequence with better efficiency of the system? - Pramanick, Biswajit; Brahmachari, Koushik; Kar, Sudeshna; Mahapatra, B. S. (Journal of applied phycology, 2020)
Producing rice grain with superior quality along with higher productivity is very much needed to improve the food and nutrient security. Therefore, this experiment was designed to determine the effect of seaweed sap derived from the red seaweed Kappaphycus alvarezii (K–sap) on quality improvement of rice grown under rice–potato–greengram crop sequence. The experiment consisted of 12 treatments using K–sap and chemical fertilizer application in a randomized complete block design replicated thrice. The study was conducted at Uttar Chandamari village, India, during two consecutive years of 2013–2014 and 2014–2015. It was found that the maximum amounts of physical quality attributes, viz. hulling, milling, head rice recovery and biochemical quality attributes like amylose and carbohydrate contents of rice, were found with 7.5% K–sap + 100% RDF (recommended dose of fertilizer). This treatment also exhibited the highest system productivity. Concerning the efficiency of the system, it was documented that the maximum values of agronomic efficiency, physiological efficiency and recovery fraction of nutrient used were recorded in 7.5% K–sap + 50% RDF, 0.0% K–sap + 50% RDF and 7.5% K–sap + 100% RDF, respectively. It was also evaluated that the foliar spraying of K–sap at 2.5, 5 and 7.5% rate along with 100% RDF showed the positive nitrogen (N) balance of the system. From this study, it was observed that the foliar application of K–sap is able to improve the quality of rice besides improving yield and better system efficiency. Positive N balance was also accomplished through the application of K–sap in combination with RDF.